Response to Comment on "Detection of the Elusive Nitrogen‐Centered Radicals from Catalytic Hofmann–Löffler Reactions". Issue 40 (20th October 2020) - Bosnidou, Alexandra E.; Duhamel, Thomas; Muñiz, Kilian
Abstract : The initial steps of the catalytic Hofmann–Löffler reaction include the formation of the N ‐halogenated amine with further formation of a nitrogen‐centered radical. We had reported the presence and detection of a radical through EPR spectroscopy. Based on new data, we discuss the observed EPR signal. Abstract : The initial steps of the catalytic Hofmann–Löffler reaction include the formation of the N ‐halogenated amine with further formation of a nitrogen‐centered radical. We had reported the presence and detection of a radical through EPR spectroscopy. Based on new data, we discuss the observed EPR signal. Amination, Amines, EPR spectroscopy, Pyrrolidines, Radicals